What Is the Primary Driver of Preoperative Vancomycin Use? It’s Not Methicillin-resistant Staphylococcus aureus—or Allergy - Strymish, Judith M (Clin Infect Dis, 2020)
Factors driving vancomycin surgical prophylaxis are poorly understood. In a national Veterans Affairs cohort with manually validated data, surgical specialty (cardiac, orthopedics) and perception of high facility methicillin-resistant Staphylococcus aureus (MRSA) prevalence—not MRSA colonization—were the primary drivers of prescribing. A β-lactam allergy was the second most common reason. These data may inform perioperative stewardship.